Meningkatkan Kesehatan Mental Pada Remaja Di Lembaga Pembinaan Khusus Anak Dengan Intervensi Olahraga Rekreasi - Khoerunnisa, Dinda; Ramania, Nia Sri; Sinsuw, Esther Margaritha Livida; Ad-Dauli, Ahdan Abdillah; Winata, Bagus (Institut Teknologi Bandung, 2025)
This study examines the effectiveness of recreational sports interventions in addressing mental health issues among adolescents serving sentences in Juvenile Correctional Facilities (LPKA). Adolescents in prison tend to experience significant emotional stress, which can potentially worsen their mental health conditions. Sports are considered a practical and effective intervention method as they can trigger the release of serotonin and endorphins, hormones that play a role in improving mood. The research sample consisted of 20 male juvenile inmates at LPKA Bandung, aged 15-19 years, who participated in an eight-week recreational sports program. Measurements were conducted using the DASS-42 questionnaire to evaluate levels of anxiety, stress, and depression. The analysis results showed that the sports intervention significantly reduced anxiety (p-value = 0.000) but did not have a significant effect on stress and depression (p-value > 0.05). These findings suggest that recreational sports can be an effective intervention for reducing anxiety among adolescents in correctional settings; however, additional approaches are needed to address stress and depression. This study makes an important contribution to the development of sports-based rehabilitation programs in correctional facilities.